ANTAGONISME ANTARA KUMBANG AMBROSIA XYLEBORUS SP. DAN JAMUR BIRU YANG MENYERANG DOLOK TUSAM (PINUS MERKUSII) - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1994)
Freshly cut logs of tusam (Pinus  merkusii) are very susceptible to the infestation of the ambrosia beetle Xyleborus sp.  and blue stain fungi. An observation showed that both wood deteriorating organisms might infest a same log simultaneously, but they did not inhabit the same area. They have their own area which are separated from one to another. There is an indication that any parts of logs having been infested by the fungi will not be suitable any more for  the beetle's host.  It seems that the ambrosia beetle is deterred or repelled by the presence of the blue stain fungi  infestation, or at least,  the beetle responds unfavorably to the  fungi.